Sleep deprivation reduces vagal tone during an inspiratory endurance task in humans. Issue 10 (25th April 2021) - Westphal, Willy-Paul; Rault, Christophe; Robert, René; Ragot, Stéphanie; Neau, Jean-Philippe; Fernagut, Pierre-Olivier; Drouot, Xavier
Abstract: Study Objectives: Sleep deprivation alters inspiratory endurance by reducing inspiratory motor output. Vagal tone is involved in exercise endurance. This study aimed to investigate the effect of sleep deprivation on vagal tone adaptation in healthy subjects performing an inspiratory effort. Methods: Vagal tone was assessed using Heart Rate Variability normalized units of frequency domain component HF (high frequency) before, at the start, and the end of an inspiratory loading trial performed until exhaustion by 16 volunteers after one night of sleep deprivation and one night of normal sleep, where sleep deprivation reduced the inspiratory endurance by half compared to the normal sleep condition (30 min vs 60 min). Results: At rest, heart rate was similar in sleep deprivation and normal sleep conditions. In normal sleep condition, heart rate increased during inspiratory loading task; this increase was greater in sleep deprivation condition. In normal sleep condition, vagal tone increased at the beginning of the trial. This vagal tone increase was absent in sleep deprivation condition. Conclusions: Sleep deprivation abolished vagal tone response to inspiratory load, possibly contributing to a higher heart rate during the trial and to a reduced inspiratory endurance. Clinical Trial Registration: NCT02725190.